THE UVEITIS â PERIODONTAL DISEASE CONNECTION IN PREGNANCY: CONTROVERSY BETWEEN MYTH AND REALITY - Sutedjo, Widyawati; Prahasanthi, Chiquita; Utomo, Daniel Haryono (Institute of Topical Disease, 2012)
Background: Recently, It had been recognized that oral infection, especially periodontal disease are potential contributing factors to a variety of systemic diseases, such as cardiovascular and cerebrovascular diseases, pregnancy problem, diabetes mellitus type 2, etc.Â However, the adverse effect of periodontal disease toward uveitis still not clearly understood especially if happens during pregnancy.Â Interestingly, in Indonesia, there is still a myth that pregnant women should not get any dental treatment, therefore, it may deteriorateÂ periodontal disease during pregnancy.Â Purpose: to explain the possible connection between periodontal disease and uveitis and increasethe awareness of these problems during pregnancy that could be understood by doctor and laymen.Â Reviews: literatures revealed thatÂ dental infection can caused uveitis via metastatic spread of toxin and inflammatory mediators. Additionaly, more recent investigationÂ reported that the neural system may also stimulated by oral infection. In the orofacial regions theres trigeminal nerve complex thatÂ also related to the orbital region, thus may also involved in the uveitis pathogenesis. The effects of periodonto pathogens toxins towardimmunocompetent cell and nerves had also been reported by researcher. Moreover, pregnant women are more susceptible to periodontalÂ disease, therefore maintaining oral hygiene and dental monitoring is a mandatory.Conclusion: in woman who susceptible to uveitis,Â periodontal disease may exacerbate the symptoms especially in pregnancy. Therefore simple explanation about connection of oralÂ infection-systemic diseases especially in pregnancy should be widespread among Indonesian people.